Metodologias de custos e formação de preços nas micro e pequenas empresas da industria de confecção de Teresina-PI - Eulálio Neto, Manoel (2007)
The price decisions as part of the management process of companies include, among other aspects, to know the costing and pricing ways, methods and methodology appropriate to the features of the company, of the business and of the market where they are penetrated. Under these circumstances, this work is intended to expose the Costing and Pricing Methodologies used by the Micro and Small Industrial Clothing Manufacturing Companies, which participate in the SEBRAE GEOR Project. The researches were accomplished bibliographically, through the study of the literature on the theme and also a field research by means of a questionnaire. An interview with managers and trade union leaders of the companies researched was carried out. From what was studied and researched, it has become evident that most of these companies use the definite costing method, and the pricing methodology applied is that represented by the mathematic formula in which the selling price equals the total costs, plus profit margin. Thus, it can be concluded that the methodologies applied for the balancing of the costs and pricing are the most appropriate to the bulk of these companies, in addition to being an auxiliary management instrument.